1985
DOI: 10.1095/biolreprod33.1.112
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Activation of Female Reproduction by Males in a Marsupial, The Gray Short-Tailed Opossum (Monodeiphis Domestica)1

Abstract: Although social factors are known to influence reproduction in a number of eutherian mammals, the effect of these factors on marsupial reproduction has not heretofore been studied. In this study, the temporal pattern of births and of the appearance of vaginal estrus following pairing with a male were examined in the gray short-tailed opossum, a small Brazilian didelphid. Although the estrous cycle is approximately 32 days long in this species, 75% of conceptions occurred within 9 days and 91.6% within 13 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 4 publications
3
41
0
Order By: Relevance
“…Even in this amenable species generation ofovulation on demand has so far been unobtainable. Reports have shown that the presence of a male activates oestrus as evidenced by behaviour and pregnancy (L. M. Baggott, unpublished observations), and by inference as seen from exfoliative vaginal cytology and pregnancy (Fadem, 1985). However, in isolation, females have been claimed to exhibit oestrous cycles as indicated by exfoliative vaginal cytology ranging from 10 to 32 days in length (Fadem & Rayve, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Even in this amenable species generation ofovulation on demand has so far been unobtainable. Reports have shown that the presence of a male activates oestrus as evidenced by behaviour and pregnancy (L. M. Baggott, unpublished observations), and by inference as seen from exfoliative vaginal cytology and pregnancy (Fadem, 1985). However, in isolation, females have been claimed to exhibit oestrous cycles as indicated by exfoliative vaginal cytology ranging from 10 to 32 days in length (Fadem & Rayve, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Male-induced oestrus has been reported previously for one marsupial, Monodelphis domestica, in the Didelphidae (Fadem, 1985). The oestrous cycle is approximately 32 days long in this species, yet 91-6% of conceptions occur within 13 days of pairing, and isolated females do not show a regular oestrous cycle (Fadem, 1985(Fadem, , 1987.…”
Section: Oestrus In Females Isolated From Malesmentioning
confidence: 56%
“…The oestrous cycle is approximately 32 days long in this species, yet 91-6% of conceptions occur within 13 days of pairing, and isolated females do not show a regular oestrous cycle (Fadem, 1985(Fadem, , 1987.…”
Section: Oestrus In Females Isolated From Malesmentioning
confidence: 90%
“…andFADEM (1985) used successfully in our laboratory (JONES and MUNGER, 1985). Ten days following the initial contact between the male and female, the male was removed from the cage.…”
Section: Methodsmentioning
confidence: 99%